(±)-5-bromo-2-(5-fluoro-1-hydroxyamyl) Benzoate Protects Against Oxidative Stress Injury in PC12 Cells Exposed to H2O2 Through Activation of Nrf2 Pathway - Qi, Saidan; Zhang, Xiaojiao; Fu, Zhenzhen; Pi, Anran; Shi, Feiyan; Fan, Yanan; Zhang, Jiahua; Xiao, Tingting; Shang, Dong; Lin, Meng; Gao, Na; Chang, Junbiao; et al. (Frontiers in Pharmacology, 2022)
Background: Oxidative stress is associated with the pathogenesis of ischemic stroke. (±)-5-bromo-2-(5-fluoro-1-hydroxyamyl) benzoate (BFB) is a novel compound modified by dl-3-n-butylphthalide (NBP). Here, we hypothesized that BFB may protect the PC12 cells against H2O2-induced oxidative stress injury through activation of the Nrf2 pathway. Methods: We measured the cell viability and levels of lactate dehydrogenase (LDH), malondialdehyde (MDA), glutathione (GSH), and reactive oxygen species (ROS) to determine the construction of the H2O2-induced models of oxidative stress in PC12 cells. Additionally, apoptotic cell death, mitochondrial membrane potential, and cellular morphology were examined to determine the effect of BFB on oxidative stress injury in H2O2-treated PC12 cells. The expression levels of Nrf2-related and autophagy-related genes and proteins were detected using real time quantative PCR (RT-qPCR), Western Blot, and immunofluorescence analyses. Results: Our study showed that BFB treatment reduced the elevated levels of MDA, LDH, and ROS, and decreased cell viability and GSH in H2O2-treated PC12 cells. We also observed the elevated expression of Nrf2 pathway-related factors and intranuclear transitions and found that Nrf2 inhibitors (ML385) could block the protective effect of BFB. The inhibitory effect of BFB on oxidative stress may be partially regulated by Nrf2 activation, and the initiation and induction of autophagy. Conclusion: BFB inhibited H2O2-induced oxidative stress injury in PC12 cells by activating the Nrf2 pathway, initiating and inducing autophagy, suggesting that BFB may be a promising therapeutic agent in treating neurological disorders like cerebral ischemia.